Role of Sericulture in the Indian Economy - Reddy, Y. Praveen; Parasuramudu, M. (Journal for Research in Applied Sciences and Biotechnology, 2024)
Sericulture, often known as silk farming, involves raising silkworms to make silk. Out of the five states that contribute to the majority of India's silk production—Karnataka, Andhra Pradesh, Tamil Nadu, West Bengal, and Jammu & Kashmir -98.5% comes from mulberry sericulture. Silk plays a vital role in Indian culture and tradition, with a rich history spanning over five millennia. Sericulture, especially in Karnataka, supports farmers' livelihoods and has significant economic potential. However, climate change poses a serious threat to global ecosystems, endangering species and affecting industries like sericulture. The Author uses the study variables for their study and also questionnaires, and statistical tools like SPSS and Excel for data presentation and calculation respectively also used statistical techniques like, Factor Analysis, Descriptive analysis, and Relatively Analysis. Sericulture enhances income, crop diversification, sustainability, and land use efficiency, supported by government policies and training. Sericulture is vital to India’s rural development, job creation, and exports. It supports millions of rural households, especially women and marginalized communities, by generating consistent income. As one of the world’s top silk producers, India benefits from government-backed sustainable practices, making sericulture crucial to its economy.